Acceptability and Organoleptic Properties of a Herbal Drink Formula Made from Averrhoa bilimbi Leaves with Turmeric Addition as a Healthy Drink - Niken Dwi Prasiska; Dhini Prasetiya Ningrum; Lusifa Anggraini; Luthfi Assyaukani; Zalfa Aqilla Putri Zain; Pri Hardini; Arya Ulilalbab (Ficco Public Health Journal, 2026)
Background Previous studies have shown that Averrhoa bilimbi leaves can help lower blood pressure. These leaves also act as diuretics and antioxidants. Combining Averrhoa bilimbi leaves and turmeric is expected to create a herbal beverage healthy drink. This study aimed to analyze the organoleptic and acceptability tests of a functional herbal drink made with Averrhoa bilimbi leaves and turmeric that could benefit health. Methods: The research employed an experimental quantitative design with a factorial design (one factor). A total of 30 respondents participated by completing a questionnaire. Sampling was done using a convenience sampling method. Results: There were significant differences in color, aroma, and taste (p < 0.05), but not in texture (p = 0.104). The formulation without Averrhoa bilimbi leaves (P0) was the most preferred overall compared to P1 and P2. Conclusions: The addition of turmeric significantly affected the color, aroma, and taste, but not the texture. The formulation without turmeric (P0) was the most preferred by the panelists.